Old-fashioned cures and proven home remedies : that lower your cholesterol and blood pressure, improve your memory, and keep diabetes and arthritis under control - FC&A Medical Pub (Peachtree City, GA : FC&A Medical Pub., 2007)
A collection of old fashioned home remedies, from kissing a frog to cure your asthma, to ironing your underwear to kill the fungus that causes yeast infections.--
Keywords: Naturopathy -- Popular works